THE THEN AND NOW OF MAIZE LEAF DEVELOPMENT - Langdale, J (2005)
Most of what we know about the mechanistic basis of maize leaf development has been revealed in the last twenty years. This review provides a historical account of advances in the area and highlights the contributions that have enhanced our general understanding of plant developmental biology.